Play characteristics in the genre structure of girl’s diary - Rabenko, Tatyana Gennadyevna; Gorovaya, Yana Olegovna (Жанры речи, 2023)
The relevance of the research is determined by its inclusion into the theory of natural written speech, namely, into the study of genre organization of this type of writing and speech activity. The genre of a girl’s diary, considered as a written implementation of a phatic playful behavior, is described from the point of a dominant determinant approach. In the aspect of external determination, the genre playful intent is researched through its social environment analysis. In the aspect of internal determination, the dependence of genre features within a discourse unit is revealed. The playful intention is regarded as a genre dominant, at the level of which the interrelation of extralinguistic and linguistic features of the text is analyzed. The authors of the paper claim that a girl’s diary, reflecting the process of a girl’s socialization in her girlhood, construes a phatic play space where the “adult” topics can be discussed in confidential communication with the people of the same age. The play is embodied at the level of extralinguistic conditions of a text generation: the spatial and temporal organization of diary communication (the functioning of the diary in a closed socio-cultural environment); the selection of communication participants; the deployment of communication, considering its regularity and some freedom of speech actions of the participants. The play principle is represented at the linguistic level of speech, within the framework of the structural and content arrangement of the text (the tendency of the sections of the girl’s diary to keep to the phatic play format of communication; specific genre types of texts); the linguistic embodiment of the genre (usage of youth slang; a multi-coded text; a language play). As a result, the play dominant of a girl’s diary determines the intermediate position of diary communication between the real and unreal areas in the language consciousness of the diary community members. The ways of a play discourse structuring the girl’s diary are based on the rules prescribed by the genre standards; they aim at modeling a virtual version of reality, which correlates with the socio-cultural status of the diary community members.